Speed and Process of Melting Arctic Sea Ice - Dirk Notz (Latest Thinking, 2019)
(en)The Arctic sea ice is the ice that is floating on the Arctic Ocean. In recent decades, this pack ice has been disappearing very rapidly. So the question arises when the Arctic sea ice will be completely gone. apache-tomcat-10.1.28 bin conf google3d3484531fe2f8a1.html google75618b12b4dbf37f.html internationalization-tool log metadata-dump-transformations metadata-schema.zip nohup.out oersi-backend oersi-etl search-index-import-scripts tomcat DIRK NOTZ has examined this using the Arctic summer sea ice in September as an example. As he explains in this video, his research group combined satellite observations with model simulations and found a clear linear correlation between the loss of Arctic sea ice and carbon dioxide emissions. apache-tomcat-10.1.28 bin conf google3d3484531fe2f8a1.html google75618b12b4dbf37f.html internationalization-tool log metadata-dump-transformations metadata-schema.zip nohup.out oersi-backend oersi-etl search-index-import-scripts tomcat For each ton of CO2 we emit, we make about three square meters of Arctic sea ice disappear. From this linear relationship, the researchers could extrapolate the amount of carbon dioxide that can still be emitted before the Arctic sea ice is completely gone in summers. For the first time, these findings present very intuitive numbers that make clear the impact every individual has on global warming. This LT Publication is divided into the following chapters: 0:00 Question 1:11 Method 3:32 Findings 6:18 Relevance 8:46 Outlook